Social class in applied linguistics - Block, David, 1956- (New York : Routledge, 2014)
'Publications on language and identity generally focus on global language and culture flows, and are seldom informed by political economy. Additionally, social class, as an identity inscription, is ignored. This book argues that the increasing socioeconomic inequality, which has come with the consolidation of neoliberal policies and practices worldwide, requires changes in how we think about identity. Proposing that social class should be brought to the fore as a key construct, the book opens with an in-depth theoretical discussion of the concept, before tying it to areas of applied linguistics such as world Englishes, second language acquisition, multilingualism and language teaching'--
Includes bibliographical references (pages 176-190) and index.
Keywords: Applied linguistics -- Social aspects; Language and languages -- Study and teaching -- Social aspects; Language and languages -- Study and teaching -- Economic aspects; Language and culture -- Social aspects; Social interaction; Sociolinguistics